Digital Intimate Publics and Social Media
XXVIII, 304 p. 14 illus., 5 illus. in color.
Keywords: This book explores emergent intimate practices in social media cultures. It examines new digital intimacies as they are constituted, lived, and commodified via social media platforms. The study of social media practices has come to offer unique insights into questions about what happens to power dynamics when intimate practices are made public, about intimacy as public and political, and as defined by cultural politics and pedagogies, institutions, technologies, and geographies. This book forges new pathways in the scholarship of digital cultures by fusing queer and feminist accounts of intimate publics with critical scholarship on digital identities and everyday social media practices. The collection brings together a diverse range of carefully selected, cutting-edge case studies and groundbreaking theoretical work on topics such as selfies, oversharing, hook-up apps, sexting, Gamergate, death and grief online, and transnational family life. The book is divided into three parts: ‘Shaping Intimacy’, ‘Public Bodies’, and ‘Negotiating Intimacy’. Overarching themes include identity politics, memory, platform economics, work and labour, and everyday media practices.